Identifying Risk Factors for the Development of Breast Cancer among Women Attending Hiwa Hematology/Oncology Hospital in the Sulaimaniyah, Iraqi Kurdistan - Saeed, Deman Ahmed; Sheikha, Anwar Kader Ibrahim (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Breast cancer is the commonest female malignancy that affects 1 in 20 globally, with one out of every eight women in the west being a victim of it. To our knowledge, there is limited published data regarding the effect of risk factors on the prevalence of Breast Cancer among Iraqi Kurdish women. Objectives: This study aims to identify the risk factors that might affect most women Breast Cancer in our region. Patients and Methods: This cross-sectional study was conducted on 400 women diagnosed with breast cancer at Hiwa Hematology/Oncology Hospital in the Sulaimaniyah province, Iraqi, from February 14th, 2021 to June 1st, 2022. Risk factors were studied in women who visited the Clinical Oncology Department. Results: Patients' mean ± SD age at an early breast cancer detection was 47.33 ± 9.9 years. Most patients (89.3%) had no smoking history, 50.7% were passive smokers, only 0.3% had a history of alcohol consumption, 78% experienced anxiety, and 58% were physically inactive. Marriage and gynecological history were not protective factors. Family history of breast cancer was negative in 72.5% of patients; lactation in 75.5%, and several children lactated (31.0%) had no protective role. Regarding dietary habits, daily consumption of sweets (49.5%) and fat (45.2%) seemed to be risk factors. Red meat and poultry (84.8%) with fast food (79.3%) >2 times weekly were particularly relevant. However, daily consumption of fruits (80.7%) and vegetables (76.0%) seemed to have a preventive role in breast cancer. Conclusions: Physical inactivity, passive smoking, anxiety and dietary habits were significant risk factors for the development of breast cancer among Iraqi Kurdish women. Actions aimed at enhancing physical activity and controlling other modifiable risk factors seems to be essential to reduce these risks.
Keywords: Breast cancer; risk factors; cross sectional study; Hiwa Hospital